Amine-modified mesoporous silica for adsorption of copper from aqueous solutions - Da'na, Enshirah (University of Ottawa (Canada), 2008)
During the last few decades governments all around the world have increased concerns about water shortages and pollution. Consequently, they issued a multitude of environmental legislations and regulations, land and water-use planning measures, and other environmentally related procedures. The objective of this work was to contribute in developing efficient adsorbent for heavy metal ions from wastewater. Two different kinds of adsorbents were studied: MCM-41 (Mobil Catalytic Material number 41) mesoporous silica whose pores have been expanded by a post-synthesis hydrothermal treatment in the presence of N,N-dimethyldecylamine (DMDA), and 3-aminopropyltrimethoxysilane (AMP) grafted MCM-41 after being pore expanded and calcined. The pore-expanded MCM-41, (PE)MCM-41, (i.e., containing DMDA) has been tested as adsorbent for Cu2+ cations. Regeneration ability and factors affecting the stability of this material such as pH and stirring time have been investigated. The results showed that (PE)MCM-41 is fast, sensitive, and high capacity adsorbent. However, it is not an appropriate material for environmental applications due to its poor stability in aqueous solutions. Further studies using calcined and pore-expanded MCM-41, (CPE)MCM-41, silica as support for grafting AMP have been carried out. A systematic investigation of the amine loading as a function of the relative amount of AMP and water used during the grafting procedure was carried out. The surface characteristics, AMP loading, Cu2+ adsorption capacity, CO2 adsorption capacity, and rate of CO2 adsorption were determined for all materials. Surface area, pore size and pore volume decreased significantly from 950 m 2/g, 11.3 nm and 2.16 mL/g for unmodified (CPE)MCM-41 to 783 m 2/g, 7.4 nm and 1.54 mL/g for the materials grafted under dry conditions in the presence of 1.0 mL AMP/g silica, and to 730 m2/g, 6.34 nm and 0.77 mL/g for the materials grafted under wet conditions in the presence of 2.0 mL AMP/g silica and 0.4 mL water/g silica. The maximum amine loading, CO2 adsorption capacity and Cu2+ adsorption capacity suggested that the optimum grafting conditions are 2 mL AMP/g silica and 0.4 mL of water/g silica, and that any excess of water or amine added to the grafting mixture has negative effect on the adsorption performance of the material. Two approaches have been investigated to recycle the copper loaded adsorbent: treatment with acidic solution and treatment with complexing agent, ethylenediamine-tetra acetic acid tetra sodium salt (EDTA). The results showed a significant drop in the adsorption capacity after the first regeneration cycle. With further testing of the material, it was concluded that the (CPE)MCM-41 is not stable when being in contact with water and thus, even the material was still loaded with amine, structural changes of the material caused the amine to become inaccessible for Cu2+ or CO2 molecules. So, further work is still required to improve the stability of this material in water or to use more robust material.
Keywords: Engineering, Chemical.; Engineering, Environmental.